Life experiences and transitions of adult migrant learners through a biographical learning perspective - Barkoglou, Georgia; Gravani, Maria (Adult Education Discourses, 2020)
The purpose of this paper is to explore adult migrants’ learning in light of their life experiences and transitions, drawing from the narratives of two migrant learners who attended ‘Odysseus’ solidarity school in Greece. The presented research harnesses the biographical learning theory and adopts a Bakhtinian, dialogical way of presenting the data under three themes: wars and identity struggles, religious beliefs, migration and language learning in the host country. The findings revealed that adult migrants’ life experiences and transitions constitute a learning process, which enhances transformative learning of ‘being’, through a process of ‘perspective and identity struggles’. It is also found that the accumulated experiences and transitions as well as adult migrant learners’ previous educational capital are in constant relation to the way they experience language learning in the programme.